Transport of inorganic acids through polybenzimidazole (PBI) based membranes by chemo-dialysis - Chendake, Yogesh J.; Kharul, Ulhas K. (Desalination and Water Treatment, 2012)
A process of chemo-dialysis involving poly(benzimidazole) (PBI) as a chemically active membrane material is proposed for the transport of inorganic acids. These membranes possessing basic nature selectively bind acid molecules present in the feed solution due to acid-base interactions. They are transported across the membrane by concentration gradient as the driving force. The transported acid molecules are stripped away from other side of the membrane surface by a suitable stripping agent or water. Effects of nature of feed acid (pK(a), molecular size), its concentration in the feed solution and the nature of stripping agent (base or water) on acid transport properties are presented. Membranes showed appreciable transport rates for three acids, viz., H2SO4, HCl and HNO3. The fluxes for different acids varied from 16.1 to 140.7 g/m(2) h under different operating conditions. Most significantly, there was no transport of non-acidic solutes such as NaCl or glucose. This could be made possible since these solutes neither get sorbed in the membrane matrix, nor does the membrane exhibit any porosity for the transport to occur through pores. This resulted in practically infinite selectivity of transported acid over the non-acidic solutes. Use of water as the stripping agent allows recycling of the acid, making the process economically attractive. Moreover, possible recovery of acid and its reuse eliminated the requirement of acid neutralization and disposal; which is a routine practice followed today. Thus, this process of chemo-dialysis is economically attractive and environmentally benign.
Keywords: Acid transport; Chemical interaction; Chemo-dialysis; Inorganic acids; Membrane; Polybenzimidazole

Transforming covalent organic framework into thin-film composite membranes for hydrocarbon recovery - Biswal, Bishnu P. (Separation Science and Technology, 2018)
We, for the first time, employed chemically stable covalent organic framework (COF) (TpPa-1) as a transport-active phase within the polymer (styrene-butadiene rubber; SBR) matrix to make TpPa-1@SBR thin-film composite (TFC) membranes. Three composite membranes, viz., TpPa-1(30)@SBR, TpPa-1(50)@SBR, and TpPa-1(70)@SBR have been prepared with varying COF content. These membranes were characterized for gas permeance and results were compared with the pristine SBR-based TFC membrane. The fully organic nature of chemically stable COF offered good compatibility with the host polymer matrix (SBR) and resulted into flexible TFC membranes even at 70% of COF loading; compared to the other porous material (MOFs or Inorganic fillers), it is appreciable.
Keywords: Covalent organic framework; hydrocarbon recovery; propylene–propane; styrene-butadiene rubber; thin film composite

Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.